2013
DOI: 10.5578/mb.4438
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shigella Strains Isolated in Ankara, Turkey by Antimicrobial Resistance Models, Plasmid Profile Analysis and Pulsed-Field Gel Electrophoresis

Abstract: Shigella is one of the most important causative agents of diarrhea especially in childhood. Since man is the main reservoir of Shigella and human to human transmission is possible, Shigella can easily spread in public and cause outbreaks. In this study, a total of 60 Shigella strains isolated in Ankara, Turkey by years 2001, 2008 and 2009 were investigated by their antimicrobial susceptibility profiles, plasmid profile analysis (PPA) and pulsed-field gel electrophoresis (PFGE). For epidemiological investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
4
0
2
Order By: Relevance
“…In a study conducted in Turkey in 2002, resistance to TMP-SMX was reported to be 90.4 percent, whereas sensitivity to ampicillin was 86.4 percent, sensitivity to cefotaxime was 98 percent and sensitivity to ciprofloxacin was 100 percent (4). No resistance to gentamicin, ceftriaxone, nalidixic acid, imipenem or ciprofloxacin was reported in a 2008 study, whereas in a 2012 study of 60 Shigella isolates, no resistance to ciprofloxacin and gentamicin was reported, while the rate of resistance against cefotaxime was 22.2 percent (9,12). This finding suggests an emerging resistance to cefotaxime and ceftriaxone in Turkey.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study conducted in Turkey in 2002, resistance to TMP-SMX was reported to be 90.4 percent, whereas sensitivity to ampicillin was 86.4 percent, sensitivity to cefotaxime was 98 percent and sensitivity to ciprofloxacin was 100 percent (4). No resistance to gentamicin, ceftriaxone, nalidixic acid, imipenem or ciprofloxacin was reported in a 2008 study, whereas in a 2012 study of 60 Shigella isolates, no resistance to ciprofloxacin and gentamicin was reported, while the rate of resistance against cefotaxime was 22.2 percent (9,12). This finding suggests an emerging resistance to cefotaxime and ceftriaxone in Turkey.…”
Section: Discussionmentioning
confidence: 98%
“…Shigella species can develop an antibiotic resistance through such transposable DNA segments as plasmid, transposon and integron, and so the antibiotic susceptibility pattern of Shigella species is variable. Empirical antibiotherapy should be initiated considering the local antimicrobial resistant profile (9). According to US National Antimicrobial Surveillance system data, 41 percent of Shigella species are resistant to ampicillin, 48 percent are resistant to TMP-SMX and 2 percent are resistant against ciprofloxacin, whereas ceftriaxone resistance was reported to be less than 1 percent in 2010 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Shigella türleri plasmid, transpozon, integron gibi hareketli DNA parçaları aracılığıyla antibiyotiklere hızla direnç geliştirebilir bu nedenle Shigella türlerinin antibiyotik duyarlılıkları değişkendir. Ampirik antibiyotik tedavisine lokal antimikro-biyal direnç göz önünde bulundurularak başlanılmalıdır (9). Amerika Birleşik Devletleri (ABD)'nde ulusal antimikrobiyal direnç izleme sisteminin verilerine göre 2010 yılında Shigella türlerinin %41'inde ampisilin, %48'inde TMP-SMZ, %2'sinde siprofloksasin direnci bildirilirken seftriakson direnci %1'den az saptanmıştır (10).…”
Section: Discussionunclassified
“…Ülkemizde 2002 yılında yapılan bir çalışmada TMP-SMZ direnci %90.4 saptanırken, ampisilin duyarlılığı %86.4 sefotaksim-seftriakson duyarlılığı %98, siprofloksasin duyarlılığı %100 olarak bildirilmiştir (4). 2008 yılında yapılan bir çalışmada gentamisin, seftriakson, nalidiksik asit, imipenem ve siprofloksasine karşı direnç olmadığı gösterilmiş, 2012 yılında yapılan 60 Shigella izolatının değerlendirildiği başka bir çalışmada siprofloksasine ve gentamisine karşı direnç saptanmazken, sefotaksime %22.2 direnç saptanmıştır (9,12). Bu durum ülkemizde de sefotaksim ve seftriaksona direnç gelişmekte olduğunu göstermektedir.…”
Section: Discussionunclassified
“…The developed pentaplex PCR assay is robust and is capable of providing information about target genes essential for the identification of the Shigella genus and the three Shigella species responsible for the majority of shigellosis cases [42]. Pulsed-field gel electrophoresis (PFGE) is convenient for evaluation of the clonal relatedness of the strains; however, in such geographical areas where the same clone is in circulation, use of antibiotic resistance typing and/ or plasmid profile analysis together with PFGE would be useful for precise discrimination of Shigella strains [43,44].…”
Section: Discussionmentioning
confidence: 99%